Transorbital Intracranial Penetrating Injury from a Homemade Gun: A Case Report - Trakulpanitkit, Avika; Sungkaro, Kanisorn (Journal of Health and Allied Sciences NU, 2022)
A transorbital intracranial penetrating injury (TOPI) is an unusual traumatic brain injury that requires multidisciplinary management. TOPI may cause traumatic cerebrovascular injury (TCVI) and fatal brain damage with a high mortality rate. Herein, the authors described an 8-year-old male patient who was injured from a handmade gun; a projectile (marble) had penetrated the left frontal base via the left orbit. TOPI caused left anterior cerebral artery compression. A transorbital approach with an intraoperative transcranial approach on standby was performed to remove the foreign body. Postoperative intensive broad-spectrum antibiotics were administrated, and the patient made an uneventful recovery. In summary, TOPI is an uncommon TBI that risks TCVI. Intracranial vascular investigation should be performed before surgical management, and postoperative complications, such as meningitis, brain abscess, and delayed pseudoaneurysm, should be monitored.
Keywords: penetrating brain injury; orbital injury; traumatic cerebrovascular injury; traumatic brain injury